Asuhan Keperawatan pada Tn. T Keluarga Tn. T dengan Gangguan Sistem Muskuloskeletal : Gout Arthritis di Desa Kalibuntu Rt 04 Rw 03 Kecamatan Losari Kabupaten Brebes - Vicky Liza Nabila; Tati Karyawati; Arisnawati Arisnawati (Jurnal Ventilator, 2024)
Gouty arthritis or gout is a joint disease caused by high levels of purines in the blood. A person is said to be suffering from gout if the uric acid level in their body exceeds the normal limit, the normal limit is 7 mg/dL for men and less than 6 mg/dL for women. Excessive uric acid can cause a buildup of purines in the joints and other body organs, causing pain and inflammation in the joints. This condition can make the joints feel painful when moved and can also cause joint abnormalities and disabilities (Efendi et al., 2022). In Central Java, the prevalence of gout sufferers is approximately 2.6 - 47.2%, which varies in various populations (Zakiudin et al., 2024). Based on data from the Kecipir Community Health Center, the prevalence of gouty arthritis at the Kecipir Community Health Center in 2023 will reach 13.67%. The percentage of residents in Kalibuntu Village who suffer from gouty arthritis in 2023 will reach 24.3% in old age (Kecipir Community Health Center, 2023).